2022
DOI: 10.3390/molecules27030668
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Drug Repurposing Approach: Investigation of Mycobacterium tuberculosis FadD32 Targeted by FDA-Approved Drugs

Abstract: Background: Despite the enormous efforts made towards combating tuberculosis (TB), the disease remains a major global threat. Hence, new drugs with novel mechanisms against TB are urgently needed. Fatty acid degradation protein D32 (FadD32) has been identified as a promising drug target against TB, the protein is required for the biosynthesis of mycolic acids, hence, essential for the growth and multiplication of the mycobacterium. However, the FadD32 mechanism upon the binding of FDA-approved drugs is not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…directions [78]. Thus, the region of 0.5 to 1.0 represents a strong correlation, whereas the region of −0.5 to −1.0 shows a strong reverse correlation [79].…”
Section: Dynamic Cross-correlation Matrixmentioning
confidence: 97%
“…directions [78]. Thus, the region of 0.5 to 1.0 represents a strong correlation, whereas the region of −0.5 to −1.0 shows a strong reverse correlation [79].…”
Section: Dynamic Cross-correlation Matrixmentioning
confidence: 97%
“…SRB in combination of Rifampicin and Isoniazid resulted in increased killing of the M.tb by inhibiting ABCG2 efflux pumps of the bone-marrow mesenchymal stem cells (BM-MSCs) . A recent study reported fatty acid degradation protein D32 (FadD32) as another target of SRB …”
Section: Repurposed Drug Candidates Against Tuberculosismentioning
confidence: 99%
“…97 A recent study reported fatty acid degradation protein D32 (FadD32) as another target of SRB. 104 Another anticancer drug Bortezomib is a proteasome inhibitor that is used for treating multiple myeloma. 105 This drug inhibits the growth of tumor cell by affecting (NFkB) signaling pathway of activated B cells and by inhibiting interleukin (IL)-6 signaling.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
See 1 more Smart Citation
“…Drug repositioning, in other words, drug repurposing, is a set of methods that enable us to investigate the use of drug molecules that have been clinically approved or whose phase studies are in progress, outside of their medical indications. It provides a great advantage in terms of both time and cost compared to the detection of a completely new drug molecule, since it works with molecules that have been clinically and preclinically determined to be safe [25][26][27].…”
Section: Introductionmentioning
confidence: 99%